Pelatihan Trik Penjualan dan Pembuatan Buku Ajar Di Madrasah IbtidaiyahMuhammadiyah 02 Paciran - Santoso, Subhan Adi; Chotibuddin, Mohammad (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
The high number of educational institutions in an area, especially in the Paciran region, has implications for the level of competition in getting new prospective students. Every institution must be able to build school branding as the best place according to the educational needs of prospective new students and parents of students. Several schools in the region do not yet have competent teachers as textbook authors. So this service activity aims to build teacher skills in selling and manufacturing textbooks as well as at Madrasah Ibtidaiyah Muhammadiyah 02 Paciran. Community service activities are carried out in the form of offline training at the Paciran 02 Muhammadiyah Elementary School location. The results of the Devotion show that there is an increase in the ability of the teacher in selling and making textbooks as an effort to increase teacher competence in the learning process in class.